Nem tudo que reluz é vidro : mudanças sociais e introdução de artefatos vítreos na Salvador Oitocentista - Silva, Railson Cotias da (2014)
The present investigation aims to, from an archaeological perspective, observe and understand the processes of social change in the city of Salvador of eight hundred, through from the glass’s interpretative potential. Aims to understand behaviors and social practices related to modernity in the nineteenth century in the Salvador city through from the analysis of the vitreous material recovered at house 14, in the São Francisco Street - Centro Histórico de Salvador. The approach enabled understand features and peculiarities of consumption behavior in the 19th century in Salvador through the vitreous objects, as containers of information on everyday living space and of the changes in Brazilian cities, under socio-economic, political and cultural aspects, immersed in the construction of a project of modernity imported.